Speech Prosody 2014 2014
DOI: 10.21437/speechprosody.2014-107
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic Patterns in Native and Non-Native Mandarin Speech

Abstract: When analysing human spoken communication the focus on the linguistic side lies on speech with its verbal message, whereas the focus on the non-linguistic side usually is on the visually transported information such as gestures and facial expression. However, speech, especially in talk-in-interaction, also features numerous nonverbal vocalisations including various forms of laughter and inhalation noises as their most frequent forms. Although nonverbal vocalisations are usually short in duration they may provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
1
2
0
1
Order By: Relevance
“…Pauses filled with breath noise were longer than those without, as expected, and the analysis also revealed that in fluent phases the vast majority of pauses contains audible inhalation -which requires a reinterpretation of the terms "unfilled" and "silent" pauses that are often mentioned in the literature [2,3,4,5]. Future studies have to show further details of the acoustic content of "silent" pauses, particularly the production of tongue clicks [14].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Pauses filled with breath noise were longer than those without, as expected, and the analysis also revealed that in fluent phases the vast majority of pauses contains audible inhalation -which requires a reinterpretation of the terms "unfilled" and "silent" pauses that are often mentioned in the literature [2,3,4,5]. Future studies have to show further details of the acoustic content of "silent" pauses, particularly the production of tongue clicks [14].…”
Section: Discussionsupporting
confidence: 68%
“…In step 2, all pauses were annotated for whether they contained one or more of the following categories: silence, audible inhalation, clearly identified audible exhalation, and clicks, which occur rather frequently (cf. [14]) but were not considered for further analysis here. In addition there was the category of unclear cases.…”
Section: Annotationmentioning
confidence: 99%
“…Nonverbal vocalizations, on the other hand, are largely unconstrained by linguistic structure (e.g., Pell et al, 2015;Scott, Sauter, & McGettigan, 2010). They are produced at the glottal/subglottal level with reduced volitional control of the vocal tract configurations (Trouvain, 2014). A lack of volitional control and linguistic constraints on nonverbal vocalizations leads to greater acoustic variability in nonverbal expression of emotions compared to prosodic expressions of emotions (e.g., Jessen & Kotz, 2011;Lima et al, 2013).…”
Section: Nonverbal Vocalizations Versus Speech Prosodymentioning
confidence: 99%
“…Definimos las expresiones fónicas no verbales o vocalizaciones no verbales ('nonverbal vocalisations') como aquellos elementos no verbales con correlato fónico (Sauter et al 2010;Trouvain, 2014;Meneses y Igarashi, 2006;Kohler, 2008) que contribuyen a la identificación perceptiva de una determinada emoción.…”
Section: Segundo Nivel: Expresiones Fónicas No Verbalesunclassified